Applicability of Constructivist-Oriented Teaching in the Process of Educational Transformation in Malaysia - Jamaluddin, Nor Sa'adah; Li Na (International Business Education Journal, 2023)
The education industry is an important sector that contributes to the development of a country. Educators and students are among the key players who are important and should be given priority in the education industry. Thus, to explore this situation, concept papers related to aspects of the learning environment covering the applicability of constructivist-oriented teaching in the process of educational transformation in Malaysia are given emphasis by researchers. This paper emphasizes the literature review of previous researchers in providing an overview related to the development of constructivist-oriented teaching among educators which ultimately opens space for readers to build hypotheses to continue research in the future; relationship between implementation of constructivist-oriented teaching towards students achievement.